Modeling the Association between EFL Instructors' Foreign Language Teaching Enjoyment and Humor Styles - Mehdi Solhi; Majid Elahi Shirvan (National Research University Higher School of Economics, 2023)
Background: Positive psychology in the field of applied linguistics has recently shifted its focus from L2 learners to L2 teachers as teachers have been revealed to be a pivotal external affordance for the emergence of learners' positive emotions such as enjoyment. Exploring the link between teacher-related constructs can provide deep insights into L2 teachers' emotional agency within L2 classroom context. Purpose: The current study seeks to examine the association between English as a foreign language (EFL) instructors' enjoyment of foreign language teaching (i.e., personal enjoyment, student appreciation, and social enjoyment) and humor styles (i.e., self-enhancing, affiliative, aggressive, and self-defeating humor styles). Materials and Methods: In order to examine this association, 244 (151 males and 93 females) Turkish EFL instructors voluntarily completed self-report scales measuring their foreign language teaching enjoyment and humor styles. Results: Results of the structural equation modeling (SEM) indicated that higher levels of student appreciation and social enjoyment are correlated with higher levels of affiliative and self-enhancing humor. In addition, greater degrees of personal enjoyment, student appreciation, and social enjoyment are correlated with lower levels of aggressive humor, while self-defeating humor was unrelated to any of the enjoyment indices. There was also no significant gender difference for any humor styles. Conclusion: The findings are discussed in view of implications for teacher well-being.